Navigating Online Business Frontiers: Unraveling Consumer Protection Patterns and CSR Strategies in a Digital Era - Kosasih, Jaylu; Rosnawati, Emy; Fiddinia, Irta (Proceedings of The ICECRS, 2023)
In this comprehensive bibliometric analysis, conducted through VOSviewer, we explore the intricate landscape of consumer protection in online businesses with a focus on Corporate Social Responsibility (CSR) strategies. Examining 205 journal articles and conference proceedings from 2017 onwards, our study unveils a significant surge in research activities in the realm of online business law. Adam Lindgreen emerges as a prominent contributor, with the University of Nottingham leading in scholarly output. The analysis centers on 383 online business cases, predominantly concerning divorce-related matters, emphasizing the pressing need for legal frameworks in digital commerce. Our findings not only provide a nuanced understanding of evolving consumer protection challenges but also underscore the pivotal role of CSR strategies. This research serves as a crucial foundation for future policy-making, offering essential insights for global scholars and practitioners alike.Highlights : Significant Research Surge: This study uncovers a notable increase in research activities, emphasizing the growing importance of consumer protection and legal frameworks in the digital business landscape. Prominence of CSR Strategies: The analysis highlights the pivotal role of Corporate Social Responsibility (CSR) strategies, underscoring their relevance in addressing evolving challenges and ensuring ethical practices in online businesses. Policy Implications: Serving as a foundational resource, this research provides essential insights for policymakers, scholars, and practitioners, guiding future strategies and policies in the realm of online consumer protection and business ethics. Keywords: Consumer Protection, Online Business Law, Corporate Social Responsibility (CSR), Digital Commerce, Legal Frameworks